'Local hunting' and community-based natural resource management in Namibia: Contestations and livelihoods. Issue 101 (May 2019) - Lubilo, Rodgers; Hebinck, Paul
Highlights: 'Poaching' is analytically inadequate to understand local hunting. Recorded data in Even Books are socially constructed and cannot be taken at face value. Hunting manifests contestations of the distributional politics of conservancies. Hunting hinges on an ontological foundation that contrasts with the predominant conservation discourse. Abstract: The argument in this paper is not commonly made in the conservation literature. We argue that 'poaching' and 'illegal hunting' are inadequate concepts for understanding why local forms of hunting persist despite their being banned and criminalised. A 'poacher' 'poaches' because a set of institutionalised rules recognises and identifies him or her as such. Instead, we propose to use the concept 'local hunting' and 'local hunters'. We also argue that conservation policies and specifically the creation of environmental subjects, conservancy's distributional politics and a contrasting ontological foundation of community-based conservation play keys role in explaining the continuity of 'local hunting'. More space is needed to situate local hunters and their hunting practices and motivations in the broader conservation discourse and policies.